PEMETAAN STRATEGI PEMASARAN TOKO SEMBAKO YOGAS JAYA - Cokki Cokki; Andrea Yogas; Felix Adrean; Joshua Steven Angriawan; Filipus So (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
This community service activity was done to map out the marketing strategy of Yogas Jaya grocery shop. The community service team made 6 components of marketing strategy mapping which included external marketing environment analysis, company analysis, customer analysis, competitor analysis, differentiation and positioning, and marketing mix analysis. The results of the activities show that Yogas Jaya grocery store already has a marketing strategy, but not all components of the strategy are implemented. The team suggest further actions to the strategy mapping that had been done, such as asking for consumer feedback and a more in-depth analysis of each component of the marketing mix. As a piece of practical advice, the shop is advised to consider online shopping opportunities.